Catalyst-Inspired Charge Carriers for High Energy Density Redox Flow Batteries - Popov, Ivan A.; Davis, Benjamin L.; Mukundan, Rangachary; Batista, Enrique R.; Yang, Ping (Frontiers in Physics, 2019)
We introduce a theoretical design approach aiming at improving energy density of redox flow batteries (RFBs) via the utilization of redox noninnocent ligands capable of stabilizing a metal center in a wide range of oxidation states. Our findings suggest that this promotes the possibility of multiple redox events as well as high open circuit voltages. Specifically, we have proposed two Fe-coordination complexes (I, Fe(Me2Pytacn)(C2N3H2), and II, Fe(H2pmen)(C2N3H2)) combining two different types of ligands, i.e., catalyst-inspired scaffolds and triazole ring, which were previously shown to promote high and low oxidation states in transition metals, respectively. These complexes exhibit as many as six theoretical redox events in the full range of charge states +4 → –2, several of which reside within the electrochemical window of acetonitrile. Electronic structure calculations show that the Fe center exhibits oxidation states ranging from the very rare Fe4+ to Fe1+. Values of the reduction potentials as well as nature of the redox events of both complexes is found to be similar in their high +4 → +1 charge states. In contrast, while exhibiting qualitatively similar redox behavior in the lower 0 → –2 range, some differences in the electronic ground states, delocalization patterns as well as reduction potential values are also observed. The calculated open circuit voltages can reach values of 5.09 and 6.14 V for complexes I and II, respectively, and hold promise to be experimentally accessible within the electrochemical window of acetonitrile expanded by addition of ionic liquids. The current results obtained for these two complexes are intended to illustrate a more general principle based on the simultaneous utilization of two types of ligands responsible for the stabilization of high and low oxidation states of the metal that can be used to design the next-generation charge carriers capable of supporting multi-electron redox and operating in a broad range of charge states, leading to RFBs with greater energy density.